Celah dalam Penegakan Hukum Maritim: Analisis Praktik Manipulasi Automatic Identification System (AIS) pada Kasus Kapal MT Arman 114 - Fatiya Maulidya Putri; Gia Novitri Amelia; Dien Zaidan Asshiddiqie (GLOBAL SCIENTS PUBLISHER, 2026)
The MT Arman 114, captured in Natuna waters in July 2023, was proven to have conducted illegal oil transfer and waste dumping, while simultaneously manipulating its AIS data to make its position appear as if it were in the Arabian Sea, even though the vessel was actually located in Indonesian waters. This study examines the legal qualification of AIS manipulation under Indonesia's legal system as well as the implications of disregarding this offense in the Batam District Court Decision Number 941/Pid.Sus/2023/PN Btm. The findings show that the Shipping Law and Minister of Transportation Regulation Number 18 of 2022 only provide administrative sanctions in the form of a maximum fine of IDR 75 million, which creates no deterrent effect. In fact, Article 35 of the ITE Law can substantially qualify AIS Spoofing as an information crime offense with a threat of up to 12 years imprisonment. However, the panel of judges in their decision completely ignored the AIS manipulation offense and only convicted the captain under the Environmental Law. The implications are very serious, including weakened crime prevention effects, the emergence of legal uncertainty, and the disruption of Indonesia's position as a coastal state under international maritime law. This study recommends integrating the ITE Law into maritime law enforcement to close the legal loophole that has been exploited by dark fleet vessels.